2007
DOI: 10.1186/1479-5876-5-49
|View full text |Cite
|
Sign up to set email alerts
|

The histone deacetylase inhibitor belinostat (PXD101) suppresses bladder cancer cell growth in vitro and in vivo

Abstract: Background: Treatment options for patients with recurrent superficial bladder cancer are limited, necessitating aggressive exploration of new treatment strategies that effectively prevent recurrence and progression to invasive disease. We assessed the effects of belinostat (previously PXD101), a novel histone deacetylase inhibitor, on a panel of human bladder cancer cell lines representing superficial and invasive disease, and on a transgenic mouse model of superficial bladder cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 38 publications
(46 reference statements)
5
44
0
Order By: Relevance
“…The dose-dependent upregulation of p21 in tumour cells in the present study are in line with a decreased tumour growth rate after 4-PB treatment (18). Likewise, overexpression of p21 was detected after treatment of bladder and prostate cancer with belinostat, another HDACi (35,36). The present study shows an initial dose-dependent increase within the first 24 h followed by a delayed decrease of p21 upregulation after 24 h. One possible explanation is a sustained protein degradation in the extracellular space in the surroundings of accumulating apoptotic and necrotic cells.…”
Section: Discussionsupporting
confidence: 88%
“…The dose-dependent upregulation of p21 in tumour cells in the present study are in line with a decreased tumour growth rate after 4-PB treatment (18). Likewise, overexpression of p21 was detected after treatment of bladder and prostate cancer with belinostat, another HDACi (35,36). The present study shows an initial dose-dependent increase within the first 24 h followed by a delayed decrease of p21 upregulation after 24 h. One possible explanation is a sustained protein degradation in the extracellular space in the surroundings of accumulating apoptotic and necrotic cells.…”
Section: Discussionsupporting
confidence: 88%
“…71,72 In vitro studies have demonstrated that DNA methylation and histone acetylation cooperate in regulating the expression of several genes in prostate-derived cell lines. For example, both histone deacetylase inhibitors (FK228, TSA, PXD101) and a DNA hypomethylating agent (5-azacytidine) exhibited various growth inhibitory effects by inducting apoptosis or p21 induction in vitro 73,74 and in vivo. 74 …”
Section: Dna Hypomethylation In Bcmentioning
confidence: 99%
“…High expression levels of class I HDACs correlated with tumour dedifferentiation and higher proliferative fractions (measured by Ki-67) in urothelial carcinoma, which is in line with in vitro studies showing that high HDAC activity leads to tumour dedifferentiation and enhanced tumour cell proliferation [28][29][30]. Despite the growth inhibitory effects of HDAC-i demonstrated in various cell lines including bladder cancer cells, a broad expression analysis of this attractive target has not been conducted yet [12][13][14][15][16]31,32].…”
Section: Discussionmentioning
confidence: 72%
“…In contrast to these findings, a more recent study of Xu and colleagues reported no difference of expression in the expression levels of HDAC-2 between normal urothelial and bladder cancer tissue as assessed by immunohistochemistry [13]. Few studies have found an effect for HDAC-inhibitors (HDAC-i) in urothelial cancer cell lines [12,[14][15][16][17], however, a broad expression analysis of HDACs in urothelial carcinomas has not been conducted so far. In addition, there is no study available on the prognostic relevance of class I HDACs in bladder cancer.…”
Section: Introductionmentioning
confidence: 93%